Odpowiedź :
Odpowiedź:
1.
[tex]\frac{3}{4}x - \frac{2x+3}{4} = \frac{1}{4}[/tex]
[tex]3x-2x-3=1[/tex]
[tex]x=4[/tex]
2.
[tex]\frac{x+2}{9} + \frac{x-1}{3} = 1 [/tex]
[tex]\frac{x+2}{9}+\frac{3 (x-1)}{9}=1[/tex]
[tex]\frac{x+2+3x-3}{9}=1[/tex]
[tex]4x-1=9[/tex]
[tex]x=\frac{5}{2}[/tex]
3.
[tex](2x-1)(2-3x)=(2-3x)(2x+3)[/tex]
[tex]-6 x^2+7 x-2=-6 x^2-5 x+6[/tex]
[tex]12x-8=0[/tex]
[tex]x=\frac{2}{3}[/tex]
Odpowiedź:
[tex]1)\\\\\frac{3}{4}x-\frac{2x+3}{4}=\frac{1}{4}\ \ /\cdot4\\\\3x-(2x+3)=1\\\\3x-2x-3=1\\\\x=1+3\\\\x=4\\\\\\2)\\\\\frac{x+2}{9}+\frac{x-1}{3}=1\ \ /\cdot9\\\\x+2+3(x-1)=9\\\\x+2+3x-3=9\\\\4x-1=9\\\\4x=9+1\\\\4x=10\ \ /:4\\\\x=\frac{10}{4}\\\\x=\frac{5}{2}\\\\x=2\frac{1}{2}[/tex]
[tex]3)\\\\(2x-1)(2-3x)=(2-3x)(2x+3)\\\\4x-6x^2-2+3x=4x+6-6x^2-9x\\\\7x-6x^2-2=-5x+6-6x^2\\\\7x-6x^2+5x+6x^2=6+2\\\\12x=8\ \ /:12\\\\x=\frac{8}{12}\\\\x=\frac{2}{3}[/tex]